Simulation of a permanent magnet flux-switching machine with reduced outer stator leakage flux - Lindner, Andreas; Hahn, Ingo (2014 International Symposium on Power Elektronics, Electrical Drives, Automation and Motion (SPEEDAM 2014), 2014)
A small size permanent magnet flux-switching machine is designed with the aim to reduce the undesired leakage flux outside the stator. Different design alternatives are considered using a C-core type permanent magnet flux-switching machine. The leakage flux outside the stator of a permanent magnet flux-switching machine can effectively be reduced by altering the stator structure. To preserve the high torque capability of the flux-switching machine different design modifications of the stator structure have to be applied. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.simula_46
Keywords: C-core; EMC; FSPM design; leakage flux; switched-flux machine